SOLVING THE FORMULA: AN ANALYSIS OF MYSTERY STRUCTURE ON MURDER ON THE ORIENT EXPRESS - Muhammad Sayyid Fathan Fadhlullah; Zahwa Bilbina Putri Baheransyah; Agung Dwi Nugroho (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
This article discusses Kenneth Branagh's film Murder on the Orient Express (2017) through John G. Cawelti's popular formula theory, particularly in the context of the mystery genre. This study aims to examine how the narrative structure typical of the detective genre—consisting of the stages of crime, investigation, and resolution—is adapted in the medium of film. By utilizing Cawelti's theory, which emphasizes the combination of convention and innovation, this analysis shows that the film retains the main elements of the mystery formula while introducing aesthetic and moral variations that reflect contemporary values. The use of cinematic techniques such as temporal manipulation, limited perspective, and mise-en-scène enhances the audience's experience in following the investigation. Additionally, the film's theme of alternative justice adds a complex ethical dimension to Agatha Christie's classic narrative. This study confirms that Murder on the Orient Express is not merely a passive adaptation but a critical and relevant reinterpretation of the genre formula within the context of modern popular culture.